2016
DOI: 10.5551/jat.30585
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Paraoxonase 1 Activity Following Consumption of Recommended Amounts of Mixed Meals in Healthy Males

Abstract: Aim: Postprandial lipid level increases induce oxidative stress, which is involved in atherogenesis.The antioxidant properties of paraoxonase 1 (PON1) have attracted attention. However, changes in postprandial PON1 levels differ across prior studies, and changes in PON1 lactonase activity, potentially relevant to PON1 physiology, after the consumption of ordinary meals are unknown. Herein we evaluated postprandial serum lipid levels and PON1 changes following mixed-meal consumption of the amounts recommended f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In contrast to the previous report 41 ) , the present study failed to show an association between AREA and MDA-LDL as surrogate marker for oxidative stress, while AREA at baseline was significantly inversely associated with hsCRP. Furthermore, Kameyama et al reported that postprandial increases in AREA and postprandial decreases in PON-1 lactonase activities in healthy men 43 ) . The baseline blood samples were collected at non-fasting state on admission in 92% of patients, and AREAs at baseline in these patients were slightly higher compared with the AREA in fasting state at the beginning of the CR (756.2 ± 170.2 vs 727.4 ± 129.0, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the previous report 41 ) , the present study failed to show an association between AREA and MDA-LDL as surrogate marker for oxidative stress, while AREA at baseline was significantly inversely associated with hsCRP. Furthermore, Kameyama et al reported that postprandial increases in AREA and postprandial decreases in PON-1 lactonase activities in healthy men 43 ) . The baseline blood samples were collected at non-fasting state on admission in 92% of patients, and AREAs at baseline in these patients were slightly higher compared with the AREA in fasting state at the beginning of the CR (756.2 ± 170.2 vs 727.4 ± 129.0, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…While PON1 is a promiscuous enzyme, displaying esterase and lactonase activities, the current assay of its activity frequently takes advantage of the former; namely, phenylacetate is used, in which case PON1 activity is expressed as arylesterase activity [1]. On the other hand, much attention has recently been paid to lactones as physiologically relevant substrates that are still under investigation [1,2].…”
mentioning
confidence: 99%
“…In fasted blood samples, the levels of lipids, such as cholesterol and triglycerides, were enzymatically determined. Serum PON1 arylesterase activity was kinetically determined using phenylacetate by recording absorbance changes at 270 nm [2]. Similarly, PON1 lactonase activity was kinetically determined using 5-(thiobutyl) butyrolactone by recording absorbance changes at 405 nm [2].…”
mentioning
confidence: 99%
See 2 more Smart Citations